The power of movement - Catherine Warner (Ateliers d'Anthropologie)
Philippe Sagant’s research demonstrated the importance of mobility in building Himalayan societies and cultures. He understood migration as shaping village relations across time and space, and in this way, he historicized eastern Himalayan communities as participants in new global modernities. This article draws upon Sagant’s work to offer an overview of migration in Eastern Nepal and Darjeeling in the late nineteenth and early twentieth centuries.